2003
DOI: 10.1002/jid.996
|View full text |Cite
|
Sign up to set email alerts
|

The political economy of Zimbabwe's descent into conflict

Abstract: The last two years have seen intensifying political violence in Zimbabwe. Could Zimbabwe slide further into political and economic turmoil? Or are there sufficient checks and balances in the social system to halt decline? The paper argues that the failed economic stabilization of the 1990s led to increased support for the opposition movement, especially among the middle-class and trade unionists who were hit by high inflation. The veterans of the liberation war and peasants-who are the power base of the ruling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…It has been shown that even limited land conflicts can erupt into large-scale civil strife and violence (Andre and Platteau, 1998), especially if "political entrepreneurs" capitalize on the underlying grievances to further their cause (Fred-Mensah, 1999;Daudelin, 2002, Addison andLaakso, 2003). At the same time, there are few detailed studies of conflicts relating specifically to land or efforts aiming to separate the impact of changes in the legal framework governing land relations as compared with the myriad of other factors that can have an impact on the incidence of conflict.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that even limited land conflicts can erupt into large-scale civil strife and violence (Andre and Platteau, 1998), especially if "political entrepreneurs" capitalize on the underlying grievances to further their cause (Fred-Mensah, 1999;Daudelin, 2002, Addison andLaakso, 2003). At the same time, there are few detailed studies of conflicts relating specifically to land or efforts aiming to separate the impact of changes in the legal framework governing land relations as compared with the myriad of other factors that can have an impact on the incidence of conflict.…”
Section: Introductionmentioning
confidence: 99%
“… It is also worth noting that commercial farms were crucial for employment and total agricultural production, as well as export earnings. For example, in the 1990s, commercial farms accounted for 68% of gross agricultural output and 40% of total export earnings (Addison and Laakson, 2003). …”
mentioning
confidence: 99%
“…In June 2002 around 3,000 white farmers were ordered to leave their farms (Addison and Laakso 2003), and by August 2002 the fast track land reform was completed. More than 5,000 white-owned commercial farms were seized (IRIN Johannesburg, 22 Feb 2007), and by the end of 2002, only 600 white farmers remained in the country (Sachikonye 2003).…”
Section: Box 2 Fast Track Land Reformmentioning
confidence: 99%